Electronic structure and photocatalytic activity of wurtzite Cu–Ga–S nanocrystals and their Zn substitution1. Issue 16 (28th April 2015) - Kandiel, Tarek A.; Anjum, Dalaver H.; Sautet, Philippe; Le Bahers, Tangui; Takanabe, Kazuhiro
<x xml:space="preserve">Abstract</x> Stoichiometric and gallium-rich wurtzite Cu–Ga–S ternary nanocrystals with and without Zn substitution were synthesized and their electronic structure and photocatalytic activities were investigated.